+0  
 
0
73
1
avatar

If we express 3x^2 - 8x - 2 in the form a(x - h)^2 + k, then what is a + h + k?

 Nov 24, 2020
 #1
avatar+116126 
+1

3x^2  - 8x    -2          factor out the 3

 

3 (x^2  - (8/3)x   - (2/3)  )

 

Take (1/2)  of 8/3 = 4/3...square this =  16/9....add and subtract  this inside the parentheses

 

3 ( x^2  - (8/3)x  + 16/9  - (2/3)  - 16/9)    factor the  first three terms, simplify the rest

 

3 [ ( x - 4/3)^2  -  22/9 ]       distribute the 3

 

3 ( x - 4/3)^2  - 22/3

 

a = 3      h = 4/3    k =   -22/3

 

a  +  h  +  k   =

 

3 + 4/3 - 22/3  =

 

3 - 18/3   = 

 

3  - 6   =

 

-3

 

 

cool cool cool

 Nov 24, 2020

70 Online Users

avatar
avatar